Study of (P, D) Reaction on 209Bi at 42 Mev - Sultana , Sadia Afroze; Rahman, Md Azizur (Journal of Bangladesh Academy of Sciences, 2022)
The 209Bi(p,d) 208Bi reaction has been studied with 42 MeV protons. The laboratory angles are 25°, 30°, and 35°. Energy spectra have been calculated theoretically as an incoherent sum of many shell-orbits constituents based on the Distorted-Wave Born Approximation (DWBA). An asymmetric Lorentzian form strength response function having energy-dependent spreading width is adopted in this analysis. The calculated deuteron energy spectrum is reasonably well reproduced in the direct reaction region. The agreement between the experiment and the calculated double differentials cross-sections up to all experimental points is reasonable and satisfactory, thereby yielding confidence in the theoretical models used. J. Bangladesh Acad. Sci. 45(2); 197-203: December 2021